Fluid Controls on the Heterogeneous Seismic Characteristics of the Cascadia Margin. Issue 20 (18th October 2018) - Delph, Jonathan R.; Levander, Alan; Niu, Fenglin
Abstract: The dehydration of oceanic slabs during subduction is mainly thermally controlled and is often expressed as intermediate‐depth seismicity. In warm subduction zones, shallow dehydration can also lead to the buildup of pore‐fluid pressure near the plate interface, resulting in nonvolcanic tremor. Along the Cascadia margin, tremor density and intermediate‐depth seismicity correlate but vary significantly from south to north despite little variation in the thermal structure of the Juan de Fuca Plate. Along the northern and southern Cascadia margin, intermediate‐depth seismicity likely corresponds to increased fluid flux, while increased tremor density may result from fluid infiltration into thick underthrust metasediments characterized by very slow shear wave velocities (<3.2 km/s). In central Cascadia, low intermediate‐depth seismicity and tremor density may indicate a lower fluid flux, and shear wave velocities indicate that the Siletzia terrane extends to the plate interface. These results indicate that the presence of thick underthrust sediments is associated with increased tremor occurrence. Plain Language Summary: Fluids are released from subducting oceanic lithosphere as temperature and pressure within the Earth increases. The release of these fluids is manifest by seismicity within the subducting lithosphere and nonvolcanic tremor near the subduction interface. Along the northern and southern Cascadia margin, the spatial distribution of seismicity within the slab and nonvolcanic tremor correlates with very slow shear wave velocities in the lower crust of the overriding plate. These low‐velocity zones likely represent underthrust sediments containing slab‐derived fluids. In central Cascadia, however, seismicity and tremor are relatively low, and a low‐velocity zone in the lower crust of the forearc is not observed. Our results suggest that a combination of variations in the distribution of underthrust sediments and fluid flux along the margin may be the ultimate control on the tremor and seismicity distribution along the Cascadia margin. Key Points: Low‐velocity zones in the Cascadia forearc lower crust correlate with nonvolcanic tremor density and intermediate‐depth seismicity Low‐velocity zones are thick (>10 km) and indicate the presence of fluid within oceanic crust and underthrust metasediments Low‐velocity zones, seismicity, and tremor can be linked to fluids sourced from a variably hydrated and/or permeable subducting slab